Urgency Of Undergraduate Student Resilience To Mental Health: A Systematic Literatur Review - Aditia Kharisma Meliala; Ilfiandra (Universitas PGRI Yogyakarta, 2024)
Resilience is one of the important characteristics possessed by students, to be able to survive in difficult situations, succeed, and be happy in living life. The motivation behind this research is to see the relationship between student resilience and mental health. This study uses a systematic literature review (SLR) method taken from various international literature through Google Scholar, PubMed, publish and perish and Sciendirect using the keywords